Live and Wet Markets: Food Access versus the Risk of Disease Emergence. Issue 7 (July 2021) - Naguib, Mahmoud M.; Li, Ruiyun; Ling, Jiaxin; Grace, Delia; Nguyen-Viet, Hung; Lindahl, Johanna F.
Abstract : Emerging zoonotic diseases exert a significant burden on human health and have considerable socioeconomic impact worldwide. In Asia, live animals as well as animal products are commonly sold in informal markets. The interaction of humans, live domestic animals for sale, food products, and wild and scavenging animals, creates a risk for emerging infectious diseases. Such markets have been in the spotlight as sources of zoonotic viruses, for example, avian influenza viruses and coronaviruses, Here, we bring data together on the global impact of live and wet markets on the emergence of zoonotic diseases. We discuss how benefits can be maximized and risks minimized and conclude that current regulations should be implemented or revised, to mitigate the risk of new diseases emerging in the future. Highlights: Emerging zoonotic diseases can spread from animals to humans where there is an interface allowing pathogens to jump the species barriers, and crowded conditions, where different species intermingle, increase these interfaces. Live and wet markets serve as hubs where humans and different animal species are in close proximity, but they are also crucial for food supply in many countries. Live and wet markets have been linked to the emergence of different epidemic/pandemic diseases, including coronavirus disease 2019 (COVID-19) and different subtypes of influenza A viruses, and they are also an important source of foodborne pathogens. It is time to reconsider the regulations at live and wet markets in high-risk regions to prevent future pandemics. To reduce the risks of zoonotic transmission we need improved biosecurity measurements and continuous monitoring.